2018
DOI: 10.3758/s13420-018-0358-6
|View full text |Cite
|
Sign up to set email alerts
|

Precrastination: The fierce urgency of now

Abstract: Procrastination is a familiar and widely discussed proclivity: postponing tasks that can be done earlier. Precrastination is a lesser known and explored tendency: completing tasks quickly just to get them done sooner. Recent research suggests that precrastination may represent an important penchant that can be observed in both people and animals. This paper reviews evidence concerned with precrastination and connects that evidence with a long history of interest in anticipatory learning, distance reception, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 60 publications
1
8
1
Order By: Relevance
“…By this way of thinking, precrastination may be the default, automatic, tendency in many choice situations, as suggested by Fournier et al (2018) and Wasserman (2018). Our new results suggest that this more automatic tendency can be overcome if enough cognitive resources are available to inhibit this tendency.…”
Section: Discussionsupporting
confidence: 58%
“…By this way of thinking, precrastination may be the default, automatic, tendency in many choice situations, as suggested by Fournier et al (2018) and Wasserman (2018). Our new results suggest that this more automatic tendency can be overcome if enough cognitive resources are available to inhibit this tendency.…”
Section: Discussionsupporting
confidence: 58%
“…Rosenbaum et al (2014) attributed such precrastination in humans to the desire to complete a subgoal early and, although the bucket carrying task would not appear to be of this kind, precrastination in humans may be encouraged by tasks in which subgoals may be forgotten or circumstances might arise that prevent the subgoal from being completed later. If such forethought is required for precrastination, one might not expect other animals to show such an effect (but see Wasserman, 2019). In the present research, however, the pigeons did precrastinate.…”
Section: Discussioncontrasting
confidence: 60%
“…If such forethought is required for precrastination, one might not expect other animals to show such an effect (but see Wasserman, 2019). In the present research, however, the pigeons did precrastinate.…”
Section: Discussionmentioning
confidence: 99%
“…Wasserman and Zentall here hypothesize that organisms will precrastinate if reward will be available soon (as found by Wasserman & Brzykcy, 2015) but will procrastinate if reward will be available later (as found by Zentall et al, 2018). This view, which was inspired by and echoed by Rachlin and Green (1972), Rung and Madden (2018), and Wasserman (2018), was previewed earlier, when we indicated that one might hurry to bring in groceries (precrastination) but delay working on term papers (procrastination).…”
Section: Animal Studiesmentioning
confidence: 77%